Endovascular Treatment of Anterior Communicating Artery Aneurysms: A Single-Center Experience from a Developing Country - Saghebdoust, Sajjad; Barani, Amir Reza; Mehrizi, Mohammad Ali Abouei; Ekrami, Mehran; Lajimi, Amir Valinezhad; Termechi, Gholamreza (Asian Journal of Neurosurgery, 2023)
Objective In recent years, endovascular methods have been developed to treat intracranial aneurysms. To date, results of endovascular treatment (EVT) for anterior communicating aneurysms (ACoAs) have never been investigated in Iran. Thus, we sought to assess the mid-term angiographic and clinical outcomes of patients with ACoAs who underwent EVT in a tertiary center.Materials and Methods Electronic health documents of patients with ACoAs who underwent EVT from March 2019 to July 2021 were retrospectively reviewed. Demographic and clinical characteristics of patients, procedural and clinical complications along with immediate and 12 months' postprocedural angiographic and clinical results were included in the analysis. Aneurysm occlusion status was classified based on the Raymond–Roy Occlusion Classification (RROC), and clinical outcomes were assessed using the modified Rankin Scale (mRS).Results Of 38 patients with 38 ACoAs, 32 patients (84.21%) presented with subarachnoid hemorrhage of whom 23 (60.52%) had ruptured ACoAs. EVT included simple coiling in 29 patients (76.32%), balloon-assisted coiling in 6 (15.79%), and stent-assisted coiling in 3 (7.89%). Immediate and 12-month postprocedural angiograms demonstrated complete/near-complete occlusion (RROC I and II) in 32 (84.21%) and 35 patients (97.22%), respectively. Periprocedural complications occurred in five patients (13.15%), and the mortality rate was 5.26%. Thirty-two patients (84.21%) had favorable outcomes (mRS 0–2) at the last follow-up.Conclusion EVT is a safe and beneficial procedure with favorable mid-term clinical and angiographic outcomes for ACoAs. Our results can lay the foundation for further studies in developing countries and are satisfactory enough for neurointerventionists to put EVT on the therapeutic agenda of ACoAs.
Keywords: anterior communicating artery; endovascular treatment; intracranial aneurysm; clinical outcome; angiographic outcome